Antimicrobial, antioxidant, toxicity and phytochemical assessment of extracts from Acmella uliginosa, a leafy-vegetable consumed in Bénin, West Africa - LAGNIKA, LATIFOU (My University, 2016)
Background: Acmella uliginosa (Asteraceae) is a flowering plant whose leaves are consumed as a vegetable in Benin. They are also traditionally used as an antibiotic in the treatment of infectious diseases. To evaluate the therapeutic potential and toxicity effect of this leafy-vegetable, the antibacterial, antifungal, antioxidant activities and, toxicity and phytochemical constituents were investigated. Methods: Dichloromethane, methanol and aqueous extracts of Acmella uliginosa were evaluated for their antimicrobial activity against six bacterial and six fungi strains. Antibacterial and antifungal activities were investigated by microdilution method and agar diffusion method respectively. Antioxidant activity was assessed using the 2,2-diphenyl-1-picryl-hydrazyl assay and phytochemical screening was carried out using standard procedures. Finally, oral acute toxicity at a dose of 2000 mg/kg was done according to the Organization for Economic Co-operation and Development guideline n° 423. Results: The antibacterial activity was broad spectrum, inhibiting both Gram-positive and Gram-negative bacteria. The minimum inhibitory concentration ranged from 0.625 to 5 mg/ml. The antifungal evaluation show that all the extracts inhibited mycelial growth and sporulation of fungi with percentages of inhibition ranging from 9.39 to 75.67 % and 22.04 to 99.77 %, respectively. In DPPH radical scavenging assay, the effect on reducing free radicals increased in a dose dependent manner. The percentage of inhibition of DPPH ranged from 0.94 to 73.07 %. Phytochemical screening revealed the presence of coumarin, flavonoid, naphtoquinone, anthracene derivative, saponin, lignan, triterpene and tannin. The dichloromethane and methanol extracts showed the best biological activities; they were also shown as the best extraction solvents of phytochemicals. In the acute toxicity evaluation, all animals were physically active and no deaths of rats were observed during the test. However, the aqueous extract promoted biochemical, hematological and histopathological alterations of treated rats at 2000 mg/kg body weight. Conclusion: A. uliginosa extracts contains antimicrobial, antioxidant agents and was not lethal for rats when ingested. However, according to the results obtained for biochemical, hematological, and histopathological analysis, caution is required regarding its consumption.
Keywords: Acmella uliginosa; Antifungal; Antibacterial; Antioxidant; Toxicity; Phytochemical